2019
DOI: 10.1007/s40744-019-00182-7
|View full text |Cite
|
Sign up to set email alerts
|

Spebrutinib (CC-292) Affects Markers of B Cell Activation, Chemotaxis, and Osteoclasts in Patients with Rheumatoid Arthritis: Results from a Mechanistic Study

Abstract: Introduction: Spebrutinib (CC-292) is an orally administered, covalent, small-molecule inhibitor of Bruton's tyrosine kinase (BTK), part of the B-cell and Fc receptor signaling pathways. This study evaluated spebrutinib pharmacology and mechanism of action over a 4-week treatment period in patients with active rheumatoid arthritis (RA). Methods: Primary human B cells, T cells, natural killer cells, macrophages, dendritic cells, basophils, and osteoclasts were treated with spebrutinib in vitro. Clinical pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 18 publications
1
77
0
Order By: Relevance
“…Spebrutinib (CC-292) is the first irreversible covalent oral small molecule that inhibits BTK activity in B and myeloid cells. A phase IIa study with 47 patients over the course of four weeks showed that spebrutinib inhibited cellular responses associated with BTK signaling in primary human immune cells and was well tolerated [ 254 ]. Bristol–Myers Squibb developed a reversible inhibitor, BMS-986142, and an irreversible inhibitor, branebrutinib [ 255 , 256 ] of BTK.…”
Section: Autoimmune Diseasesmentioning
confidence: 99%
“…Spebrutinib (CC-292) is the first irreversible covalent oral small molecule that inhibits BTK activity in B and myeloid cells. A phase IIa study with 47 patients over the course of four weeks showed that spebrutinib inhibited cellular responses associated with BTK signaling in primary human immune cells and was well tolerated [ 254 ]. Bristol–Myers Squibb developed a reversible inhibitor, BMS-986142, and an irreversible inhibitor, branebrutinib [ 255 , 256 ] of BTK.…”
Section: Autoimmune Diseasesmentioning
confidence: 99%
“…Safety and pharmacokinetics of GS-4059 in healthy volunteers and RA patients were evaluated in phase I placebo-controlled randomized study (NCT02626026), but no results have been posted. Spebrutinib (CC-292), although significantly reducing markers of chemotaxis and osteoclast activity, did not reach the statistically significant ACR 20 criteria (ACR20) response rate at week 4 in RA patients treatment [ 81 ]. HM71224 is a potent small molecule inhibitor BTK.…”
Section: Tsdmards Based On Jaks/mapks/nf-κb/syk-btk-targeted Theramentioning
confidence: 99%
“…AEs resulting from BTK inhibition can be followed in clinical trial of spebrutinib in RA patients [ 81 ]. It was well tolerated and most AEs like nausea, back pain, diarrhea, cough, and migraine were mild in severity.…”
Section: Tsdmards Based On Jaks/mapks/nf-κb/syk-btk-targeted Theramentioning
confidence: 99%
See 1 more Smart Citation
“…In a mouse xenograft human MM model, a combination of the BTK inhibitor CC-292 (spebrutinib, Celgene Corporation) with the proteasome inhibitor carfilzomib increased vertebral trabecular bone mass compared to carfilzomib alone and reduced tumor burden [ 10 ]. While CC-292 does not inhibit osteoclast differentiation, it inhibits the formation of the osteoclast sealing zone, thus interfering with osteoclast function and activity [ 10 ], and leading to reduced serum levels of the bone resorption biomarker carboxy-terminal collagen cross-linking telopeptide in mice [ 10 ] and humans [ 11 ]. CC-292 reduced tumor load and normalized tumor-associated expansion of T cells and monocytes, and did not affect T cell function in the adoptive transfer TCL1 mouse model of chronic lymphocytic leukemia [ 12 ].…”
Section: Introductionmentioning
confidence: 99%